Pembentukan Karakter Religius Peserta Didik di SD Muhammadiyah 3 Surakarta - Hartini, Hartini (Universitas Sebelas Maret, 2022)
Character education is an effort to apply religious, moral and ethical values to students through science, assisted by parents, teachers and the community which is very important in the formation and development of students' character. Every child has good potential from birth, but this potential must continue to be honed and socialized properly so that each child's character is formed and develops optimally. The aim of this research is to find out the formation of religious character at SD Muhammadiyah 3 Surakarta. This research is included in descriptive qualitative research. Data collection techniques use interviews, observation and documentation. The research results showed that the formation of religious character at SD Muhammadiyah 3 Surakarta through the habit of carrying out Duha prayers, reading and memorizing short letters before and after learning begins can foster religious attitudes and noble character and can shape the character of students.